SEGMENTATION AND COUNTING THE NUMBER OF TEETH PANORAMIC DENTAL IMAGE - Nur Nafi'iyah; Endang Setyati (Jurnal Ilmiah Kursor, 2018)
There are many methods for segmentation human teeth or dental radiographs. The most frequently used segmentation method is thresholding. In developing a system of segmentation in human teeth based on panoramic tooth photographs, several very important steps are needed. Segmentation is the separation of teeth from the background and separation of each tooth. The purpose of this study, which is to separate dental image per tooth by segmentation. In addition, the other most important process is feature extraction, which is the process of knowing the most important part of the image of the tooth to be processed. Stages in this study, namely: improving the image with CLAHE, then thresholding, the results of thresholding are segmented using integral projections, the results of segmentation extracted features using tooth centroid. Thresholding or binarization is changing grayscale image into binary forms, the algorithm used is iterative adhaptive thresholding. The accuracy value of the thresholding process or separating teeth from the background is 66.67%. Segmentation is done twice, namely: separating the maxilla and mandible, and separating each tooth. Separates the maxilla and mandible using a horizontal integral projection algorithm. Whereas to separate each tooth using vertical integral projection. In order for the separation process of each tooth to produce the best, the tooth panoramic photo is divided into three parts, namely: the left, right, and center. However, from the process of separation of each tooth the accuracy is 33.33%.